ANALYSIS OF THE MORTALITY OF THE Acacia mearnsii De Wild. - Schneider, Paulo Renato (2005)
The mortality probability of the Acacia mearnsii De Wild. stands was studied in permanent sample stratified at different spacings and site. The results allowed to conclude that the mortality can estimated with a probabilistic function in relation with the inverse of the diameter at breast height (d) and age (t): PM = {1+ EXP (-9,5593 . d-1 + 104,9543 . t-1)}–1. By the Pearson correlation of the mortality rate it was verified a high association with age, average diameter, average height, dominant height, basal area, volume and vital spacing. It was verified that the mortality is directly related to age, site quality and vital spacing in some periods of growth of the trees in the stand.